Estimasi Emisi Gas Rumah Kaca pada Pengelolaan Sampah Domestik dengan Metode IPCC 2006 di TPA Talang Gulo Kota Jambi - Winny Laura Christina Hutagalung; Alfin Sakinah; Rinaldi Rinaldi (Departemen Teknik Sipil dan Lingkungan, IPB University, 2020)
The waste that loaded to the Talang Gulo Landfill in 2018 is 1,012.234 m3/day and is predicted to produce Greenhouse Gas (GHG) emissions such as CH4 and N2O. The purpose of this study was to create a waste management layout, to determine the generation data and composition of waste in Jambi city and calculate the estimated amount of Greenhouse Gas (GHG). The calculation of Greenhouse Gas (GHG) emissions in this study used from Intergovernmental Panel On Climate Change (IPCC) 2006 method. Sampling results show that the average waste generation in Jambi City is 0.207 kg/person/day. Food waste, plastics, and paper were the dominant components from the composition of waste in landfill by 47,381%, 20.565%, and 13.096%. CH4 emissions generated from landfill zone VI in 2019 amounted to 4,695×10-2 Gg and would increase to 16,608×10-2 Gg in 2030. Greenhouse gas emissions generated from the composting zone consisted of 8,6×10-4 Gg CH4 and 5,16×10-5 Gg N2O in 2019 and 9,5×10-4 Gg CH4 and 5,7×10-5 Gg N2O in 2030. Emissions from heavy equipment activity in 2019 amounted to 1,065 Gg CO2. Estimates of greenhouse gas emissions are useful for taking steps to mitigate greenhouse gas emissions.